Political implications of the development of the linguistic competence of students in the educational complex - Poliakova, Ia. V.; Shugaeva, E. A.; Azmetova, R. F.; Yanova, E. A.; Klimakina, E. A,; Pashneva, S. A.; Kovalenko, I. V. (Cuestiones Políticas, 2020)
In modern conditions of rapid development of international contacts and ties in culture, politics, economics and other spheres, practical knowledge of foreign languages becomes a real necessity and an indispensable condition for a successful career. Educators and researchers in recent decades have increasingly focused on the unity of motivational-cognitive and behavioral components in the graduate's personality structure. The broader concepts reflecting this unit turned out to be "competence" and "being competent." Contextual analysis of the concepts "competence" and "professional competence" indicates that various approaches to their interpretation have now been developed. The competence-action approach could implement the conceptual idea of modernizing the teaching and learning process, that is, ensuring mastery of communicative activities through the development of a set of competences focused on opportunities, skills, needs, cognitive activity and creativity of the students with clear political implications. It is concluded that, the competence in foreign languages is based on the development of constitutive capacities, such as: linguistic, communicative, transcultural, sociocultural, intellectual, educational, professional and critical thinking.